ANALISIS TINGKAT RETURN DAN RISIKO INVESTASI PADA REKSADANA SAHAM MELALUIDUA CARA INVESTASI: LUMP Sf/MDAN SISTEM BERKALA - , Mouses Haposan Dayan ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Along with the growth of stock market in Indonesia, weather to see from financial institute point of view or society by itself, they are realized to find another alternative way to invest for the comfort of their financial future. Society awareness on the meaning of savings is upgrading towards investment act with hope of resulting the best return in the future. Many options in investments taken by capitol holder can be illustrate into many kind of investment form, such as deposit, stocks, mutual funds or any kind of investment instruments offerd by the stock market with different characteristic. The purpose of this study is to analyze the rate of return and risk of stock mutual fund investment by two way kind of placement: lump sum and systematic investment plan (January 2009-December 2011). The methods use on this study is using t test of two tailed. The data itself acknowledge from monthly statistics download from Indonesia Capital Market and Financial Institutions Supervisory Agency. The results shows that two way kind of placement for investment giving different rate of return and risk.